If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5y + -9 = 21 Reorder the terms: -9 + -5y = 21 Solving -9 + -5y = 21 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -5y = 21 + 9 Combine like terms: -9 + 9 = 0 0 + -5y = 21 + 9 -5y = 21 + 9 Combine like terms: 21 + 9 = 30 -5y = 30 Divide each side by '-5'. y = -6 Simplifying y = -6
| 6(y-1)-(2y)=6 | | I/6-k=5 | | -3(t-4)+5t=4t-4 | | 2-x+-2=8 | | -.03x=400-700 | | 5b+2=c | | -.3x=400-700 | | 3n+5=25 | | -300x=400-700 | | 7x+8=3x+36 | | 8/v=3/6 | | -30x=700-400 | | 7v^2+35-42=0 | | 30=-3(a-7) | | 6=5(a-7) | | 15x+4000=10x+10000 | | -b-4(1+7b)=228 | | 0.1x^2+5x-140=0 | | 12t(t+2)=t-10 | | -30x=400-700 | | c=450m+75 | | 15x-4000=10x+10000 | | 12t^2+24t+10=0 | | -0.3x=400-700 | | 6=-3/-5(a-7) | | -0.3x=700-400 | | 32=x+3+x+4-x | | ln(-5x-6)=ln(2-4x) | | 51200=1x+.07x | | 2x+-5=(8x+7)-x | | 3-(x/7)=(5x/7)-9 | | c=3t+25 |